The Implementation of Scientific Approach in Teaching English at SMP Muhammadiyah 2 Mlati Sleman - Roni Juliansyah (Journal of English Language and Pedagogy, 2019)
This research was aimed to describe the implementation of scientific approach and the difficulties in teaching English. The researcher used qualitative research. Subjects of this research were English teachers of SMP Muhammadiyah 2 Mlati Sleman.The data of this research  were collected by applying observation, interview and documentation. The data were analyzed by applying data reduction, data display, and conclusion based on Miles and Hubberman (1994).The findings showed that the teachers implemented scientific approach  covering the activities were as follows, (1) in the observing activity, teachers showed  prohibition pictures, English instructions and introduced in English, (2) in the asking activity, there was activity of asking and answering about the observed objects., (3) in the experimenting activity, the teachers guided the students to demonstrate, discuss and try, (4) in the associating activity, the teachers guided the students to conduct English exercise, (5) in communicating activity, students present orally. Meanwhile there were  difficulties faced by the teachers as follows, (1) lack of attractive media in the observing activity, (2) lack of students’ activiness, (3) lack of  students’ confidence and participation to experience, (4) lack of students’ vocabulary, (5) and lack of students’ attention.